2014
DOI: 10.1002/stem.1716
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell-Specific Scavenger Receptor CD36 Drives Glioblastoma Progression

Abstract: Glioblastoma (GBM) contains a self-renewing, tumorigenic cancer stem cell (CSC) population which contributes to tumor propagation and therapeutic resistance. While the tumor microenvironment is essential to CSC self-renewal, the mechanisms by which CSCs sense and respond to microenvironmental conditions are poorly understood. Scavenger receptors are a broad class of membrane receptors that are well characterized on immune cells and instrumental in sensing apoptotic cellular debris and modified lipids. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
213
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(221 citation statements)
references
References 72 publications
(94 reference statements)
8
213
0
Order By: Relevance
“…47,66 Additional biomarkers that have been studied in GBM include CD15, CD36, A2B5, L1CAM, CD44, and CXCR4. 2,6,24,35,47,51,73,78,95 Although these markers are useful in furthering our understanding of CSC function and regulation and may be involved in targets for therapies against CSCs, no single marker can definitively identify or define CSCs (Table 1).…”
Section: Glioblastoma and Cancer Stem Cellsmentioning
confidence: 99%
“…47,66 Additional biomarkers that have been studied in GBM include CD15, CD36, A2B5, L1CAM, CD44, and CXCR4. 2,6,24,35,47,51,73,78,95 Although these markers are useful in furthering our understanding of CSC function and regulation and may be involved in targets for therapies against CSCs, no single marker can definitively identify or define CSCs (Table 1).…”
Section: Glioblastoma and Cancer Stem Cellsmentioning
confidence: 99%
“…As such, malignant glioma regrowth following alkylating agent therapy (temozolomide) in mice is due to the relative resistance of CSCs to this agent (Chen et al, 2012). Moreover, many of the markers expressed by CSCs also serve as independent predictors of survival in patients with these malignancies (Hale et al, 2014; Lathia et al, 2014; Pietras et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, selective targeting seems feasible as it was found with isolated rat cardiomyocytes that sulfo-N-succinimidyl oleate (SSO) does block CD36-mediated palmitate uptake while both hexarelin, a synthetic growth-hormone releasing peptide that binds to CD36, and EP 80317, a CD36 selective ligand that inhibits cholesterol transport, each had no effect on palmitate uptake (47). Still, intervening in the CD36 subcellular recycling machinery is expected to allow a more specific approach because, in general, the proteins involved in vesicular trafficking occur in tissue-specific types.A final interesting direction of CD36 research is the field of cancer and metastasis, as there is emerging evidence that in certain types of cancer, CD36 expression drives tumor progression by increasing the availability of fatty acids and lipids (e.g., see (78,79)). In addition, in a recent study Pascual and co-workers (80) observed that a subpopulation of cancer cells with unique metastasis-initiating potential could be marked by CD36, highlighting a key role of lipid metabolism in metastatic colonization.…”
mentioning
confidence: 99%